Quest for an Indigenous Pedagogy: Learning from Tharu Festivals of Western Nepal (Journal of Tikapur Multiple Campus, 2022)
This paper attempts to evoke the underpinning pedagogy in Tharu festivals of Dangaura Tharus living in western Nepal. This study also focused on assessing the connections of the Tharus’ pedagogies with that of the formal and non-formal schools. In order to explore indigenous pedagogy embedded in Tharu festivals, using interpretivism as a research paradigm and ethnography as a research design, I engaged with the Chairperson of Guruwas (Tharu Priests), 4 Barghars (village Chief) and 4 Tharu social elites (indigenous elders) of the western Nepal as selected purposively. The required information was gathered with the help of participant observation of cultural events and in-depth interviews with Barghars and traditional healers of Tharus. I identified the pedagogy embedded in Tharu festivals like Magh, Atwari, Guriya, Anatta, Dashya, Dewari, etc. and interconnected them to social theories like conflict theory, system theory, and functionalist theory. Based on my reflection and various methodological procedures on indigenous pedagogical practices in Tharu festivals, I theorize the objectives, contents, teaching methods, evaluation process and revision process embedded in Tharu festivals as indigenous pedagogy. Based on these findings, this article recommends specific culturally responsive pedagogical practices for the teachers, educational planners, and policymakers of formal and non-formal education through bottom-up approaches. I concluded that each culture has its own pedagogical process which can be applied to the education system of the nation.